A gramática e a língua viva na perspectiva de Bakhtin: o ensino de orações coordenadas e subordinadas - Souza, Jéssica Duarte de (2019)
The teaching of syntactic analysis has long provoked an aversion to Portuguese language classes, which are often based only on traditional grammars. The studies and reflections of Mikhail M. Bakhtin (2013) shed new light on the problem, because, for the author, the study of syntax without the stylistic approach does not enrich the language of the students. It is important to remember that Bakhtin's concept of style differs from traditional conception. Still, the Russian philosopher assures that stylistics has great collaboration to give the teachers in their pedagogical work of teaching grammar. In the book Stylistic Issues in Language Teaching (2013), Bakhtin presents a method that focuses on rewriting subordinate clauses without conjunctions, modifying them into subordinates with conjunctions, showing students that in subordinates without conjunctions there is greater expressiveness and dramaticity in relation to subordinates with conjunctions. The purpose of this study is to understand Bakhtin's lessons as a teacher and to see how we can put them into practice in elementary school in order to lead students to glimpse other aspects of language use beyond normative grammar. The research was based on Bakhtin's studies on dialogism (2006, 2010), discourse genres (2016) and on the role of stylistics in native language classes (2013), as well as reflections on grammar types as normative de Cunha and Cintra (2016), the description by Perini (2016) and the internalized by Luft (1995). The analysis is qualitative, descriptively, through a field research, carried out in a private school, in the municipality of Itaú de Minas / MG, is composed of theoretical discussion, field research with a grammar teacher, writing proposal and analysis of the personal account produced by the students. The corpus was selected from personal reports produced by students in the writing class. The analysis of the texts was based on a personal account of some fact that occurred with them, when they were still very small, in order to see how and which expressive characteristics of the linguistic forms make up their texts. Then, through clippings of the unpunished compound periods found in the students' essay, we indicate the change in the unpunished coordination period by a conjunction period to evaluate the difference. The present work is justified by the importance that this practice adopted by the language philosopher may have in the daily life of the Portuguese Language teacher, because it makes the teaching of grammar more alive for the students. Research has shown that Bakhtinian stylistics can contribute to an active knowledge of the processes of living language and literary language. Keywords: Grammars and stylistics. Bakhtin and discursive genres. Personal reports. Stylistics and expressive intonation.